Industrial reuse of orange peel: A review of current applications - Ferreira, Emilly Brito; de Oliveira, Caroline Crivelaro; Ferreira, Kethleen Brito; da Silva, Jean Lopes; Vieira , Angelica Marquetotti Salcedo (Seven Editora, 2024)
Citrus fruits are valued globally for their high nutritional value. However, industrial processing, especially juice extraction, generates by-products that are often discarded or used in animal feed. Orange peel, a byproduct of this process, is a rich source of essential components that can be transformed into high-value bioproducts. Managing these wastes is challenging due to their high quantity, physicochemical properties, and seasonality of production. This study aims to explore the sustainable use of orange peel waste to generate new bioproducts. A literature review was conducted on the use of new technologies in orange peel waste. This encompasses several potential applications for the peel, including packaging production; use in bakery products; extraction of biologically active compounds for pharmaceutical or cosmetic use; extraction of pectin, used as an emulsifying, stabilizing, gelling and thickening agent; use in the biorefinery for the production of biodiesel, bioethanol and biogas; in the treatment of water and effluents; and in obtaining new chemical products, such as solvents. Finally, orange peel waste is a potential source for obtaining high value-added materials in various industries, contributing to a circular economy and reducing environmental liabilities. DOI:https://doi.org/10.56238/sevened2024.026-060